Statistical analysis of the key scheduling of the new lightweight block cipher - Kapalova, Nursulu; Algazy, Kunbolat; Haumen, Armanbek; Sakan, Kairat (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This research paper is aimed at studying the generation of round keys (GRK) of the lightweight block cipher (LBC), which provides an optimal balance between security, performance, and minimal costs in internet of things (IoT). For comparative analysis, the GRK of the well-known PRESENT algorithm was studied. A number of studies have been carried out to assess the cryptographic strength of encryption algorithms, however, less attention has been paid to the assessment of the reliability of GRK algorithms, which can lead to a possible weakening of a cryptosystem. A trusted GRK should issue random and independent round keys regardless of the secret key. The experiments were carried out with secret keys of low and high density, as well as random numbers. The obtained results show that the GRK of the LBC algorithm generates random round keys that successfully pass tests of the National Institute of Standards and Technology (NIST) for randomness.